Investigating the role of coping strategies, personality traits and mindfulness with self-care in leukemia patients - Khajeh Hasani Rabari, Fatemeh; Rezaei, Fatemeh; Mirzai, Fatemeh; Sedighi, Fatemeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Leukemia is one of the most common cancers, and several factors play a role in aggravating the disease process. The purpose of this study was to investigate the relationship between coping strategies, personality traits, and mindfulness with self-care in leukemia patients.Materials and Methods: The research design was descriptive-correlation. The statistical population of the research included patients with leukemia in Shariati and Sina hospitals in Tehran in the second half of 2023. 250 people were selected by the convenience sampling method. The data were collected using the Coping with Stressful Situation Questionnaire (CISS), the Neo Five-Factor Personality Characteristics Questionnaire, the Freiburg Mindfulness Questionnaire Short Form (FMI-SF), and the Self-Efficacy Self-Care Questionnaire (SUPPH) and analyzed with a step-by-step regression test with SPSS software.Findings: The results showed that the relationship between self-care and problem-oriented, emotion-oriented and avoidance strategies and the characteristics of extroversion, openness to experience, adaptability, conscientiousness and mindfulness has a significant positive relationship and a significant negative relationship with neuroticism. Also, the results showed that mindfulness, problem-oriented strategy, neuroticism, openness to experience and conscientiousness predict a total of 58% of the variance of self-care in patients with leukemia.Conclusion: Considering the effect of problem-oriented strategy, neuroticism, openness to experience and conscientiousness in self-care, it is suggested to organize courses to improve self-care in order to improve psychological health and increase self-care in patients with leukemia.